Strengthening Islamic Economic Ethics for Online Business Actors in Facing Digital Disruption - Noh, Mohd Shahid Mohd; Hidayati, Nuril; Utama, Yopi Yudha; Yuliani, Yuliani; Saka, Dijan Novia; Mutafarida, Binti; Fawaid, M. Wildan; Zunaidi, Arif; Zaenuddin, M.; Dina, Ulfi (Welfare : Jurnal Pengabdian Masyarakat, 2024)
The rapid development of digital technology presents opportunities as well as challenges for online business people, especially in maintaining business ethics according to Islamic principles. The seminar activities held at IAIN Kediri aim to strengthen understanding of Islamic economic ethics for students and online business people in facing digital disruption. The community service method used is service learning, which involves interactive learning through theory, practice and reflection. This seminar includes an explanation of the basic concepts of Islamic business ethics, group discussions to explore the application of sharia principles in online business, as well as a simulation of ethical business management. The results of the activity showed an increase in participants' understanding regarding the importance of integrity, honesty and responsibility in running an online business. In addition, this activity encourages participants to integrate Islamic values in their digital marketing strategy, creating a balance between profit and blessing. This activity makes a real contribution in empowering online business people to face the challenges of the digital era ethically and professionally.